A contribution to financial and geomechanical pit optimisation - Grenon, Martin; Ngoma Bolusala, Christian (Reading Matrix, 2020)
Surface mine financial optimisation and geomechanical design are not well integrated. This paper presents a case study where both the net present value (NPV) and the design of slopes, for various ultimate pit scenarios, were assessed based on the geological block model. In the first stage, the stability of the excavations was evaluated using limit equilibrium techniques. This resulted in the construction of susceptibility maps based on the factor of safety (FS) and the probability of failure (PF). The financial and geomechanical benefits associated with different scenarios were employed to arrive at an optimised design.